2020
DOI: 10.1101/2020.04.23.20076042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Features of 16,749 hospitalised UK patients with COVID-19 using the ISARIC WHO Clinical Characterisation Protocol

Abstract: medRxiv preprint 5 Structured abstractObjective -To characterize the clinical features of patients with severe COVID-19 in the UK.Design -Prospective observational cohort study with rapid data gathering and near realtime analysis, using a pre-approved questionnaire adopted by the WHO. Setting -166 UK hospitals between 6 th February and 18 th April 2020. Participants-16,749 people with COVID-19.Interventions -No interventions were performed, but with consent samples were taken for research purposes. Many partic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

47
462
6
31

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(546 citation statements)
references
References 11 publications
47
462
6
31
Order By: Relevance
“…Older age and pre-existing medical conditions, specifically diabetes mellitus, hypertension, ischemic heart disease, and chronic lung disease, are associated with a more severe course of COVID-19 (5a). Diabetes mellitus is one of the most prevalent comorbidities among patients hospitalized due to COVID-19 (7). Data obtained from 21 hospitals in Wuhan, China, showed that 25% of the reported COVID-19 fatalities had a history of diabetes mellitus (33).…”
Section: Afif Nakhleh and Naim Shehadehmentioning
confidence: 99%
“…Older age and pre-existing medical conditions, specifically diabetes mellitus, hypertension, ischemic heart disease, and chronic lung disease, are associated with a more severe course of COVID-19 (5a). Diabetes mellitus is one of the most prevalent comorbidities among patients hospitalized due to COVID-19 (7). Data obtained from 21 hospitals in Wuhan, China, showed that 25% of the reported COVID-19 fatalities had a history of diabetes mellitus (33).…”
Section: Afif Nakhleh and Naim Shehadehmentioning
confidence: 99%
“…1 Organ dysfunction, particularly progressive respiratory failure and acute kidney injury, is associated with the highest rates of mortality. 3,4 These manifestations have been linked to a systemic microvascular thrombosis and generalized coagulopathy, associated with a marked inflammatory response and persistent complement activation. 5 Severe disease usually occurs in the setting of certain comorbidities: obesity, diabetes mellitus, hypertension, advanced age, and male gender at any age.…”
mentioning
confidence: 99%
“…5 Severe disease usually occurs in the setting of certain comorbidities: obesity, diabetes mellitus, hypertension, advanced age, and male gender at any age. 3,4 Given those risk factors, and the spread of SARS-CoV-2 by close contact, COVID-19 was expected to affect a disproportionate number of people in lower socioeconomic classes. First, these individuals may be less able to socially distance because of housing situation, or occupation, or both.…”
mentioning
confidence: 99%
See 2 more Smart Citations